Transition Metal Transport in Plants and Associated Endosymbionts: Arbuscular Mycorrhizal Fungi and Rhizobia - González-Guerrero, Manuel; Escudero, Viviana; Saéz, Ángela; Tejada-Jiménez, Manuel (Frontiers in Plant Science, 2016)
Transition metals such as iron, copper, zinc, or molybdenum, are essential nutrients for plants. These elements are involved in almost every biological process, including photosynthesis, tolerance to biotic and abiotic stress, or symbiotic nitrogen fixation. However, plants often grow in soils with limiting metallic oligonutrient bioavailability. Consequently, to ensure the proper metal levels, plants have developed a complex metal uptake and distribution system, that not only involves the plant itself, but also its associated microorganisms. These microorganisms can simply increase metal solubility in soils and making them more accessible to the host plant, as well as induce the plant metal deficiency response, or deliver directly transition elements to cortical cells. Other, instead of providing metals can act as metal sinks, such as endosymbiotic rhizobia in legume nodules that requires relatively large amounts to carry out nitrogen fixation. In this review, we propose to do an overview of metal transport mechanisms in the plant-microbe system, emphasizing the role of arbuscular mycorrhizal fungi and endosymbiotic rhizobia.